2014
DOI: 10.1155/2014/167197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MSWI Bottom Ash Codisposed with MSW on Landfill Stabilization with Different Operational Modes

Abstract: The aim of the study was to investigate the impact of municipal solid waste incinerator (MSWI) bottom ash (BA) codisposed with municipal solid waste (MSW) on landfill stabilization according to the leachate quality in terms of organic matter and nitrogen contents. Six simulated landfills, that is, three conventional and three recirculated, were employed with different ratios of MSWI BA to MSW. The results depicted that, after 275-day operation, the ratio of MSWI BA to fresh refuse of 1 : 10 (V : V) in the land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In landfills, it is used as a stabilizing layer to protect the geomembrane, intermediate layer and also as the leachate drainage layer [ 109 , 110 ].…”
Section: Utilization Of Mswi Bottom Ash In Building Materialsmentioning
confidence: 99%
“…In landfills, it is used as a stabilizing layer to protect the geomembrane, intermediate layer and also as the leachate drainage layer [ 109 , 110 ].…”
Section: Utilization Of Mswi Bottom Ash In Building Materialsmentioning
confidence: 99%
“…When elements such as calcium (Ca), silicon (Si), magnesium (Mg), iron (Fe), aluminum (Al), and sodium (Na), which are the dominant elements in MSWIBA, are co-disposed in a MSW landfill, the risk that alkali and alkali earth metals (especially Ca) will leach intensifies (Li et al 2014;Lo and Liao 2007). Previous research has shown that at a low liquid-to-solid ratio, the leaching concentration of Ca may be as high as 5000-6000 mg/L and increases as conditions within the landfill become more acidic (Meima and Comans 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the four scenarios, improvement in the collection of MSW would be aimed at as it would eliminate scattered waste disposal. Establishment of sanitary landfills are of paramount importance regardless of implementation of recycling or incineration (Agamuthu, 2013) or combination of both approaches as there would be some material that could not be recycled (Kral et al, 2018;Turner et al, 2015;Zuberi et al, 2015) or for bottom ash from incineration that would require proper disposal (He et al, 2017;Li et al, 2014). The informal sector already plays a significant role in the recycling of MSW in Pakistan -their incorporation in the waste management hierarchy is often suggested in the literature (Masood and Barlow, 2013).…”
Section: Swm-ghg Calculatormentioning
confidence: 99%